Liberdade religiosa e discurso de ódio: uma contribuição para a formação de parâmetros razoáveis na formação normativa e aplicação judicial - Alexia Duarte Torres (2019)
The existence of variable, vague, and often inconsistent terminologies about hate speech is a challenge for the pursuit of parameters for application in judicial cases and the formation of restrictive norms, especially regarding hate speech in the religious context. In this pursuit, it is essential to reconcile the guarantee of freedom of expression with religious freedom and to allow the externalization of faith and doctrine in the public space. Thus, this dissertation is dedicated to map, first in a philosophical panorama, the main points regarded to hate speech and religious speech, and then to detail the movements and international documents generated by international groups and organizations in order to guarantee the coexistence and the exercise of freedoms in an environment of pluralistic worldviews. Once the inexistence of a consolidated understanding in Brazil on this matter has been verified, this research aims to contribute to the development of reasonable parameters that act less vaguely in the conceptualization of hate speech and do not result in the exclusion of the interaction and involvement of religious groups in the public sphere.